Pendampingan Pelatihan Literasi Digital Bagi Penderita Kanker Anak Di Rumah Kanker Ambu - Milyane, Tita Melia; Wahyuning Astuti, Sri (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Children are vulnerable age and are very easily influenced by various shows on digital media, whether they have a positive or negative impact. At the Ambu cancer home, children with cancer spend most of their time playing with gadgets/smartphones in between routine treatments. Sometimes, while waiting for treatment or examination of their disease, these children do internet searches and access various types of online games, and play social media and other online information. However, the lack of knowledge among parents of children with cancer, so children are usually free to access various shows on their smartphones without thinking about the impact that arises in the hope that shows on smartphones can make children more comfortable and can even make children forget 'for a while' the pain. But behind this, there is a big danger if children can freely access various information and digital media displays. So through this community service activity, we carry out mentoring activities for children with cancer at the Ambu cancer home so that they can sort out useful and appropriate media shows according to their age, as well as train the critical abilities of children with cancer-related to media viewing. which endangers their psychic development such as the tendency to ignore people around them, temperament, easily saddened, and so on. The digital literacy training assistance activities target children and adolescents aged 10-17 years who live in the Ambu cancer home. The activity method is carried out by providing training in the form of role-playing, and storytelling. The results of the mentoring activities are expected to increase insight and knowledge about the importance of sorting shows, games, and information from smartphones. This activity also involves the parents of the target children so that there is a synergy between the knowledge provided and the parenting pattern for the children.